Teaching Reading to Beginner Learners with Easy Methods - Khakimova Dilshoda Oybek qizi (Research Parks Publishers, 2023)
This article gives useful information about the definition of reading and teaching the easiest ways of starting reading to beginners. In the paper, methods of how to teach beginner learners to reading are also provided with clear examples.